Kendala dan Dampak Pembelajaran Daring Bagi Siswa SDN 11 Ranah Batahan - Ainul Husna; Ari Suriani; Sahrun Nisa (Jurnal Bintang Pendidikan Indonesia, 2024)
The Covid that hit Indonesia has made everything we do change drastically. There are many rules in our daily lives such as wearing masks, washing hands and maintaining distance. In addition, all areas of life are also affected, the most affected is in the field of education. The impact of covid 19 is certainly very influential for schools, even universities because online learning is carried out, this is certainly very impactful. In addition to having a great impact on online learning, there are also obstacles in implementing it, for example, students do not have mobile phones, or teachers are not proficient in using IT-based technology and many more. The impact of online learning is very diverse, the most affected is elementary school, because it is in elementary school that we start everything, both lessons and socializing. The impact of online learning, especially at the elementary level, is that students become lazy in learning, students are bored while studying, the lessons learned do not enter the brain due to lack of explanation by the teacher, student association becomes less and so on.